Economic Potential For Development Of Organic Agriculture In Food Crops And Horticulture In Supporting Sustainable Agriculture - Romadhona, Sukron (AGRIBUSINESS JOURNAL, 2024)
various parties involved in the agricultural sector about the importance of health and environmental sustainability. Agribusiness is important because of positive demands from consumers, especially the food sector. Technological developments and people's welfare have caused the demands of food consumers to change, namely not only demanding quantity but demanding quality, safety, health, and food security. The concept of development in the agricultural sector should not only focus on increasing product productivity, but also pay attention to natural balance, product quality and safety. This study uses five variables, namely revenue, costs, income, R/C ratio and ICS. The analytical method used in this study was qualitative analysis to describe the application of ICS at the research location and farmer characteristics, while quantitative analysis was performed to calculate farming costs, revenue, income, and R/C ratio. The value of the R/C ratio is 2.32, meaning that each cost of Rp. 1.00 then it can generate a profit of Rp. 2,32. An R/C ratio value of more than 1 indicates that the income generated by organic coffee farmers in Sleman Regency is higher than the costs incurred. The value of the R/C ratio is 2.32, meaning that each cost of Rp. 1.00 then it can generate a profit of Rp. 2,32. An R/C ratio value of more than 1 indicates that the income generated by organic coffee farmers in Sleman Regency is higher than the costs incurred. The value of the R/C ratio is 2.32, meaning that each cost of Rp. 1.00 then it can generate a profit of Rp. 2,32. An R/C ratio value of more than 1 indicates that the income generated by organic coffee farmers in Sleman Regency is higher than the costs incurred.Based on calculations, it is known that the average value of efficiency (R/C ratio) of organic rice farming in Sleman Regency is 6.27. This shows that organic rice farming in Sleman Regency is efficient and profitable. The value of the R/C ratio is 6.27, which means that each cost of Rp. 1.00 then it can generate a profit of Rp. 6,27. R/C ratio values that are more than 1 indicate that the income generated by organic rice farmers in Sleman Regency is higher than the costs incurred